Belief updating: does the 'good-news, bad-news' asymmetry extend to purely financial domains? - Kai Barron (Experimental Economics, 2021)
Bayes' statistical rule remains the status quo for modeling belief updating in both normative and descriptive models of behavior under uncertainty. Some recent research has questioned the use of Bayes' rule in descriptive models of behavior, presenting evidence that people overweight `good news' relative to `bad news' when updating ego-relevant beliefs. In this paper, we present experimental evidence testing whether this `good-news, bad-news' effect is present in a financial decision making context (i.e. a domain that is important for understanding much economic decision making). We find no evidence of asymmetric updating in this domain. In contrast, in our experiment, belief updating is close to the Bayesian benchmark on average. However, we show that this average behavior masks substantial heterogeneity in individual updating behavior. We find no evidence in support of a sizeable subgroup of asymmetric updators.
Keywords: C11; C91; D83; 330; economic experiments; Bayes' rule; belief updating; belief measurement; proper scoring rules; motivated beliefs